Atomic Bill : a journalist's dangerous ambition in the shadow of the bomb - Kiernan, Vincent (Three Hills, an imprint of Cornell University Press, 2022)
"An examination of the work of the New York Times reporter William L. Laurence in covering the Manhattan Project, development of the hydrogen bomb, and the early years of atomic weaponry"--